Transient Platelet Interaction Induces MCP-1 Production by Endothelial Cells via IκB Kinase Complex Activation - Gawaz, Meinrad; Page, Sharon; Massberg, Steffen; Nothdurfter, Caroline; Weber, Marion; Fischer, Claudia; Ungerer, Martin; Brand, Korbinian (Thrombosis and Haemostasis, 2002)
Activated platelets alter endothelial chemotactic and adhesive properties. Transient interaction of α-thrombin-activated platelets with endothelial cells is sufficient to induce secretion of the NF-κBregulated chemokine MCP-1. To evaluate upstream signaling events in platelet-induced NF-κB activation, we compared the effect of platelets, IL-1β or TNF-α on IκB kinase (IKK) complex activation and IκB phosphorylation/proteolysis. Kinase assays demonstrated that platelets induced a slow increase in IKK activity over 30 min, which was similar, but not identical, to IL-1β, whereas TNF-α elicited a rapid induction of IKK. Differential effects were also found on IκB-α/ε degradation, while IKK levels were unaffected. Furthermore, overexpression of kinase-inactive IKK-βKA, as well as NIKKA, inhibited plateletor IL-1β-induced κB-, MCP-1or VCAM-1-dependent transcription. Using adeno-associated virus particles for cell transduction, we found that IKK-βKA substantially reduced stimulus-induced MCP-1 secretion. Platelet-induced signaling and resulting endothelial gene expression may play a role in early atherogenesis as well as plaque progression/destabilization.Meinrad Gawaz, Sharon Page, and Steffen Massberg contributed equally to this work.
Keywords: Platelets; endothelium; NF-κB; IKK complex; adenoassociated virus